Mogroside V Alleviates Lipopolysaccharide-Induced Neuroinflammation via Inhibition of TLR4-MyD88 and Activation of AKT/AMPK-Nrf2 Signaling Pathway. (30th April 2021) - Liu, Yuanyuan; Zhang, Boxi; Liu, Jiahe; Qiao, Chunyu; Xue, Nianyu; Lv, Hongming; Li, Shize
Abstract : As innate immune effector cells in the central nervous system (CNS), microglia not only are essential for the normal development of nervous system but also act on different neurological diseases, including Alzheimer's disease (AD), Huntington's disease (HD), and other neuroinflammatory diseases. Mogroside V (Mog), a natural plant active ingredient and isolated form of Momordica grosvenori, has been shown to possess anti-inflammatory action, but few studies were carried out to investigate the effects of Mog on neuroinflammation. This study aimed to investigate the role of Mog in lipopolysaccharide- (LPS-) induced neuroinflammation and neuronal damage, revealing the underlying mechanisms. Our data indicated that Mog significantly inhibited the LPS-induced production of proinflammatory factors, such as tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), IL-18, IL-6, cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), and high mobility group box 1 (HMGB1) in BV-2 cells. We found that Mog also suppressed toll-like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), the phosphorylation of mitogen-activated protein kinases (MAPKs), adenosine 5′-monophosphate- (AMP-) activated protein kinase (AMPK), nuclear factor kappa-B (NF- κ B), and protein kinase B (AKT). Moreover, Mog also enhanced the expression of γ -glutamyl cysteine synthetase catalytic subunit (GCLC), modifier subunit (GCLM), heme oxygenase-1 (HO-1), and quinine oxidoreductase 1 (NQO1) proteins, mostly depending on the nuclear translation of nuclear factor erythroid-2 related factor 2 (Nrf2). In contrast, pretreatment with inhibitors of AKT can suppress the phosphorylation of AMPK, Nrf2, and its downstream proteins expression. In summary, Mog might play a protective role against LPS-induced neurotoxicity by inhibiting the TLR4-MyD88 and activation of AMPK/AKT-Nrf2 signaling pathway.